Unitary Boundary Pairs for Isometric Operators in Pontryagin Spaces and Generalized Coresolvents - Baidiuk, D.; Derkach, V.; Hassi, S. (Springer, 2021)
An isometric operator V in a Pontryagin space H is called standard, if its domain and the range are nondegenerate subspaces in H. A description of coresolvents for standard isometric operators is known and basic underlying concepts that appear in the literature are unitary colligations and characteristic functions. In the present paper generalized coresolvents of non-standard Pontryagin space isometric operators are described. The methods used in this paper rely on a new general notion of boundary pairs introduced for isometric operators in a Pontryagin space setting. Even in the Hilbert space case this notion generalizes the earlier concept of boundary triples for isometric operators and offers an alternative approach to study operator valued Schur functions without any additional invertibility requirements appearing in the ordinary boundary triple approach.
Keywords: Boundary pair; boundary triple; Characteristic function; Generalized coresolvent; Isometric operator; Pontryagin space; Weyl function; fi=Matematiikka|en=Mathematics|